Estudio de la formacion de los complejos intermedios durante la sintesis de alumina - J.E. Rodríguez-Páez; C. Villaquirán; J. Cobo (Materials Research, 2001)
One of the most important compounds that are used in structural ceramics is alumina. During the last years, a variety of synthesis methods have been developed to obtain raw materials with suitable characteristics in terms of particle composition, size and shape. Controlled precipitation method (CP) allows to reach these demands and with this method is possible to control the synthesis to guarantee characteristics of the ceramic powder. One stage of the CPM is the formation of intermediate complexes of cations whose oxide derives to obtain. In this work the results of study of the formation of aluminum intermediate complexes are presented. We used potentiometric and conductimetric titration to follow the advance of the process. We utilized UV-visible and IR spectroscopies to characterize the liquid phase present in the system.